From emergency to innovation: a strategic roadmap for a comprehensive telehealth platform: G. Zuccotti,1,2 A. Foppiani,1,3 C. Montanari,1,2 M. Frontini,4 V. Calcaterra2,5 | 1University of Milan; 2Buzzi Children’s Hospital, Milan; 3IRCCS Istituto Auxologico Italiano, Milan; 4Link Up s.r.l., Milan; 5University of Pavia, Italy (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2026)
The COVID-19 pandemic has decisively accelerated the adoption of telemedicine (TM), transforming it from an innovative option into a structural necessity for healthcare systems. The experience of the Vittore Buzzi Children’s Hospital shows how TM promotes equitable access to care, continuity between hospital and community services, and economic sustainability, with a particularly strong impact in pediatrics. From the emergency COD19 models, an evolutionary pathway emerged leading to a structured telemedicine platform (COD20) and a dedicated Telemedicine Center (CMT). The model integrates remote clinical care and monitoring services, including telecardiology, telenutrition, teleneurology, home-based palliative care, and advanced TM using wearable devices, tele-ultrasound, and artificial intelligence-supported tools. The results confirm effectiveness, safety, high satisfaction, and reduced hospital stays, highlighting the CMT as a key component of digital healthcare.